Dynamic feeding habits: efficiency of frugivory in a nectarivorous bat - Becker, Nina I; Rothenwöhrer, Christoph; Tschapka, Marco (Canadian journal of zoology, 2010)
Fluctuations in food availability may result in drastic changes of main dietary habits in some animals despite the lack of adaptations to alternative food types. We compared feeding efficiency between the nectarivorous bat Glossophaga commissarisi Gardner, 1962 (Phyllostomidae) that switches during nectar shortages to frugivory and the specialized frugivore Carollia brevicauda (Schinz, 1821) in a combination of behavioural experiments and HPLC (high performance liquid chromatography) analysis of fruit and faecal samples. We assessed feeding duration and employment of different bite types while animals were feeding on fruits from their natural diet. Although both bat species employed predominantly mechanically more efficient bite types, feeding efficiency (mg of fruit ingested/s) was significantly lower in G. commissarisi. Our study showed that the two bat species employed distinctly different handling and feeding strategies when feeding on the same fruits. "Frugivorous" G. commissarisi consume mostly fruit juices, but fruit anatomy seems to influence feeding efficiency. In an ecological context, the trophic shift of G. commissarisi from nectar to fruits may have implications for plant species that coevolved with bats, as well as for niche partitioning of coexisting bat species. In a more general context, our study highlights a dynamic nature of feeding niches, which might be rather common for animals living in habitats with changes in resource availability.